A study on selected cases in Malaysian construction contract / Md. Afandi Ab. Aziz - Ab. Aziz, Md. Afandi (1993)
Nowadays, the Malaysian Construction industry is expanding more rapidly in line with the dynamic growth of the nation's economy. Construction is a complex field involving big money in which dissatisfaction and disputes.